Effectiveness of remdesivir in hospitalized nonsevere patients with COVID-19 in Japan: A large observational study using the COVID-19 Registry Japan. (May 2022) - Tsuzuki, Shinya; Hayakawa, Kayoko; Uemura, Yukari; Shinozaki, Tomohiro; Matsunaga, Nobuaki; Terada, Mari; Suzuki, Setsuko; Asai, Yusuke; Kitajima, Koji; Saito, Sho; Yamada, Gen; Shibata, Taro; et al.
Abstract: Objectives: To evaluate the effectiveness of remdesivir in the early stage of nonsevere COVID-19. Although several randomized controlled trials have compared the effectiveness of remdesivir with that of a placebo, there is limited evidence regarding its effect in the early stage of nonsevere COVID-19 cases. Methods: We evaluated the effectiveness of remdesivir in the early stage of nonsevere COVID-19 using the COVID-19 Registry Japan, a nationwide registry of hospitalized patients with COVID-19 in Japan. Two regimens ("start remdesivir" therapy within 4 days from admission versus no remdesivir during hospitalization) among patients without the need for supplementary oxygen therapy were compared by a 3-step processing (cloning, censoring, and weighting) method. The primary outcome was a supplementary oxygen requirement during hospitalization. Secondary outcomes were 30-day in-hospital mortality and the risk of invasive mechanical ventilation or extracorporeal membrane oxygenation (IMV/ECMO). The data of 12, 487 cases met our inclusion criteria. The "start remdesivir" regimen showed a lower risk of supplementary oxygen requirement (hazard ratio [HR]: 0.850, 95% confidence interval [CI]: 0.798–0.906, p value < 0.001). Both 30-day in-hospital mortality and risk of IMV/ECMO introduction were not significantly different between the 2 regimens (HRs: 1.04 and 0.983, 95% CI: 0.980–1.09 and 0.906–1.07, p values: 0.210 and 0.678, respectively). Conclusions: Remdesivir might reduce the risk of oxygen requirement during hospitalization in the early stage of COVID-19; however, it had no positive effect on the clinical outcome and reduction in IMV/ECMO requirement.